New genus and four new species of anthuroid isopods (Crustacea: Peracarida) from southern Mexican Pacific - Jarquín-Martínez, Ubaldo; García-Madrigal, María Del Socorro (Zootaxa, 2021)
Anthuroid Isopoda are a poorly studied crustacean taxon in the Tropical Eastern Pacific, barely 21 species recorded, while to the southern Mexican Pacific, only eight species have been recorded. This study aims to increase knowledge of the species that inhabit the region. One hundred and one specimens from seven localities of the coast of Guerrero and Oaxaca were examined. Four new species were identified, belonging to three genera and two families: Negoescuanthura bastidai n. gen., n. sp., Colanthura gabinae n. sp., Paranthura amorensis n. sp. and P. tientai n. sp. A new genus is established, Negoescuanthura, very close to the genus Accalathura; the former is characterized by sucker-like cuticular structures on the antennal peduncle, while the latter lack these structures.